The Role of Artificial Intelligence in Enhancing Patent Lifecycle Management - Shahzeb Akhtar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative role of Artificial Intelligence (AI) across the entire patent lifecycle, from initial ideation to post-grant management. It examines how AI technologies are revolutionizing various aspects of patent processes, including brainstorming and invention disclosure, prior art searches, patent drafting, office action responses, and portfolio management. The article discusses the potential of AI to enhance efficiency, accuracy, and strategic decision-making in patent management while also addressing the ethical and legal challenges that arise from integrating AI into intellectual property processes. Key topics covered include AI-powered tools for inventors, automated patent drafting systems, predictive analytics for patent prosecution, and AI-driven portfolio optimization. The article also explores prospects, such as the potential impact of AI on patent quality and innovation, as well as the necessary adaptations in skills and workforce within the patent industry. By providing a comprehensive article overview of AI's current and potential applications in patent management, this article offers insights into how AI is reshaping the intellectual property landscape and what this means for inventors, companies, patent professionals, and the broader innovation ecosystem.
Keywords: Artificial Intelligence in Patents; Patent Lifecycle Management; AI-Assisted Patent Drafting; Automated Prior Art Search; Patent Portfolio Optimization